Risk assessment of cancer occurrence in population of young people - Lewandowska, Anna; Trawińska, Anna; Laskowska, Barbara; Lewandowski, Tomasz (Journal of Education, Health and Sport, 2017)
Introduction: Epidemiological data indicate growth of cancer appearance in young people and young adults population. According to Central Statistical Office of Poland, among teenagers between 15 and 19 years old, the number of malignant tumors reached 396 in 2008, and was “two times higher than among children aged 10-14”. Cancer diseases were the cause of death of approximately 7% of people aged 0-19 in last decade and the mortality rate has been decreasing for the past 30 years. Though, in Poland the mortality rate is still higher than in other European countries. Action aim: The goal is to evaluate the risk of cancer occurrence in population of young people. Material and method: Research has been carried out among 100 random people, aged 16-20, residing Jarosław county. The examined group had comprised of 44% of women and 56% of men. In order to obtain the research material, a standardized questionnaire has been applied including interview, enabling assessment and analysis of occurrence of cancer risk factors. Results: Brain tumor (3%), cancer of pancreas (3%), lung cancer (3%), melanoma (3%), breast cancer (2%) were most frequent types of cancer in examined women families. As for examined men families, the most frequent types of cancer were brain cancer (3%) and lung cancer (2%). When it comes to smokers, 13% of men and 9% of women confess to smoking everyday. Moreover, 2% of men and 1% of women admit drinking every single day. Additionally, 21% of men and 11% of women have contact with plant health products. Only 9% of women had admitted going to solarium in general: more than twice a week 2% of women; once a year only 7%. Conclusions: Risk of cancer occurrence, concerns both sexes. Place of residence do not influence cancer factors. Youth, to a large extent, are the most vulnerable to ultraviolet radiation. All interviewees lead healthy lifestyle. The examined youth do not do periodic health examinations.